(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Over-pumping of groundwater for domestic, agricultural and industrial consumption will lower the water table and can accelerate the movement of pollutant-laden surface water into the groundwater. In unsaturated soil, the water content is less than the soil porosity, and the soil water pressure head (matric potential) is negative, being less than that of free water at the same location. The upper most region of the soil, the unsaturated zone, is the site of important process leading to pollutant attenuation. In responding to the growing concern over deteriorating groundwater quality, groundwater flow models are rapidly coming to play a crucial role in the development of protection and rehabilitation strategies. These models provide forecasts of the future state of the groundwater aquifer systems. The present study is concerned with the development of analytical models for transport of contaminants in unsaturated porous media with non-uniform flow